Fear of COVID-19 and Anxiety in the Arabic Language Learners in Kuala Lumpur - Mokhtar, Mohd Ieruwan Mohamed (International Journal of Islamic Educational Psychology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic contributed to distress and affected mental health in many sectors, including education, which triggered fear and anxiety among learners and educators. Therefore, this research aimed to perceive mental health issues such as fear, stress, and anxiety during the pandemic, especially among learners aged between 15 to 25 from Kuala Lumpur, Malaysia. The questionnaire consisted of seven questions related to the Fear of COVID-19 Scale (FCV-19S). The respondents were invited to participate via social media platforms such as WhatsApp, Telegram, Emails, and Facebook. The link to the Google form was given to them to allow them to join the survey. Three hundred twenty-four respondents from Kuala Lumpur, Malaysia, participated in this survey to show their anxiety levels during this pandemic. The findings showed that the level of fear of COVID-19 was high and significant by using SPSS version 26. It also constructed mental health issues among the learners, decreasing their performance in education. This research is applicable to distinguish and describe the fear of the COVID-19 pandemic, which influences learners’ mental health. The findings also revealed that fear and anxiety were high and affected students’ performance.